2016
DOI: 10.1108/dpm-01-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Land use change on U.S. floodplain buyout sites, 1990-2000

Abstract: Purpose – The Federal Emergency Management Agency provides guidelines for the management of open space created through property acquisition (buyouts); however, land use decisions are primarily left to local governments manifesting in a variety of uses. The purpose of this paper is to provide a land use assessment of buyout sites, to describe the changes in those uses that have occurred during a ten-year period from 1990 to 2000, and to offer an assessment of management approaches employed acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 12 publications
1
47
0
Order By: Relevance
“…Bought-out properties reflect a range of different structure and residency types ( Fig. 3D), but most are single-family structures (18,881 properties) and primary residences (14,248). The next most common structure types include manufactured homes (i.e., mobile homes; 1837 properties), vacant land (1183), and multifamily homes (953).…”
Section: Exposure To Flood-related Hazardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bought-out properties reflect a range of different structure and residency types ( Fig. 3D), but most are single-family structures (18,881 properties) and primary residences (14,248). The next most common structure types include manufactured homes (i.e., mobile homes; 1837 properties), vacant land (1183), and multifamily homes (953).…”
Section: Exposure To Flood-related Hazardsmentioning
confidence: 99%
“…programs of managed retreat to reduce natural hazard risk are among the longest-running programs globally (12). The predominant means of government-sponsored retreat in the United States has been through voluntary buyouts of flood-prone properties (13,14). Government acquisition of flood-prone properties has generally been funded by federal agencies, especially the U.S. Federal Emergency Management Agency (FEMA), and administered by state or local governments ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…26 Falling real estate prices in at-risk areas 27,28 force some homeowners to sell at a financial loss, risk living through another storm, or abandon their homes. 25 Abandoned properties can become eyesores for which the local government has to pay to maintain, 26,29 and empty lots can destroy the sense of community. Loss of property tax revenue can make it more difficult for a town to pay for public services or other adaptations.…”
Section: Why Manage Retreat?mentioning
confidence: 99%
“…9,10,31,60 Too often, however, land where retreat occurs has not been used productively and remains derelict. 29 One study found that derelict lots were more common in a low-income minority neighborhood while open spaces in a white affluent neighborhood became parks or gardens. 87 Knowing how land is used would help evaluate and inform management approaches (e.g., how can small parcels be used beneficially?)…”
Section: One Earthmentioning
confidence: 99%
See 1 more Smart Citation